2019
DOI: 10.12659/msm.913138
|View full text |Cite|
|
Sign up to set email alerts
|

Phillygenin Exerts In Vitro and In Vivo Antitumor Effects in Drug-Resistant Human Esophageal Cancer Cells by Inducing Mitochondrial-Mediated Apoptosis, ROS Generation, and Inhibition of the Nuclear Factor kappa B NF-κB Signalling Pathway

Abstract: Background Esophageal cancer causes considerable mortality and is ranked as the 6 th most prevalent type of cancer across the world. At present, there is no effective esophageal cancer chemotherapy without adverse effects. Moreover, emergence of drug resistance among cancer is another obstacle in the treatment of esophageal cancer. Novel molecules of plant origin may prove beneficial in the development of chemotherapy for esophageal carcinoma. In this study we examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Phillygenin is a plant-derived tetrahydrofurofuran lignan. He et al reported that it could inhibit the in vitro and in vivo growth of vindesine-resistant esophageal cancer cells via inducing ROS generation and apoptosis [121]. As a natural product derived from bees, propolis was commonly used for a long time due to its various bioactivities.…”
Section: Other Related Metabolismsmentioning
confidence: 99%
“…Phillygenin is a plant-derived tetrahydrofurofuran lignan. He et al reported that it could inhibit the in vitro and in vivo growth of vindesine-resistant esophageal cancer cells via inducing ROS generation and apoptosis [121]. As a natural product derived from bees, propolis was commonly used for a long time due to its various bioactivities.…”
Section: Other Related Metabolismsmentioning
confidence: 99%
“…induced cytotoxic effects in cancer cells by increasing ROS production. Bioactive compounds such as phillygenin and plumbagin which are isolated from plants also induced cell death in cancer cells through the generation of intracellular ROS, resulting in apoptosis via a p53 dependent pathway (De et al, 2019;He et al, 2019). Understanding the nature of cell death induced by CACE and the mechanisms involved would be the next important step.…”
Section: Effects Of C Arborea Extracts On Antioxidants/oxidant Statumentioning
confidence: 99%
“…The anticancer effects of polyphenols depend not only on their chemical structure and concentration but also on the type of cancer. Lignans considered to be phytoestrogens are bioactive compounds exhibiting various anticancer properties, such as apoptosis induction and tumor growth reduction (15). Xanthones, such as α-mangostin, mediate cytotoxicity mainly via cell cycle arrest and reactive oxygen species (ROS)-induced apoptosis (16).…”
Section: Polyphenolsmentioning
confidence: 99%